(untitled) (Research, Society and Development, 2021)
Kombucha is a non-alcoholic fermented beverage traditionally produced from a sugared tea that presents a sour and refreshing taste This work aimed to develop, characterize and evaluate the sensory acceptance of Kombucha beverages made from oolong, a traditionally tea used for Kombucha production, or yerba mate tea, which is very popular and easily found herb in Brazil. The characterization was related total soluble solids (TSS), sugars, pH, titratable acidity (TA), organic acids (OA), alcohol content (AC), phenolics (PHE), flavonoids (FL), antioxidant activity (AA), besides, the sensory acceptance by potential consumers. Total soluble solids decreased 8.3% in formulation with oolong and 7.0% in formulation with yerba mate tea. The pH ranged from 4.3 and 4.5 to 2.8 and 3.1 after 14 days, respectively. Titratable acidity reached 8.97 g.L-1 in oolong tea and 6.75 g.L-1 in yerba mate tea. Acetic acid was the highest organic acid identified and quantified at the end of fermentation time. Flavonoids decreased during fermentation in both samples, while reducing capacity did not differ throughout fermentation time. Regarding the antioxidant capacity, in the formulations with oolong and yerba mate, it presented higher inhibitory capacity of the ABTS radical of 90.22 and 68.75%, while the DPPH radical inibitory capacity was 89.74% in oolong and 86.72% in yerba mate. Kombucha formulated with yerba mate tea resulted in a sour and refreshing beverage, with higher global acceptance compared to oolong tea, both drinks exhibiting antioxidant potential in vitro.